Salivary stimulatory and anti-inflammatory effects of aqueous Lilium brownii var. viridulum Baker extract for Sjögren’s syndrome: in vitro and in vivo studies - Na-Yeon Ha; Haein Jeong; Mun Seog Chang; Jinsung Kim (Brazilian Journal of Pharmaceutical Sciences)
Abstract Sjögren’s syndrome (SS) damages exocrine glands, and Lilium brownii var. viridulum Baker (Lilii Bulbus, LB) shows potential as a therapeutic agent. This study evaluated LB’s efficacy in alleviating xerostomia using non-obese diabetic/severe combined immunodeficiency (NOD/SCID) mice and human salivary gland acinar (NS-SV-AC) cells. In vitro, NS-SV-AC cells were treated with LB (1, 5, 10, 50, and 100 µg/mL) and 5-aza-2′-deoxycytidine (2 µM/mL) for 48 h. Cell viability, fluid secretion, and aquaporin-5 (AQP-5) expression were assessed. In vivo, thirty 20-week-old NOD/SCID mice received LB orally (100, 500, and 1,000 mg/kg) for 4 weeks, with salivary secretion rates measured. AQP-5 and M3 muscarinic acetylcholine receptor (M3R) expression and inflammatory mediator levels were determined using western blotting and enzyme-linked immunosorbent assay. Histopathological examination of salivary glands was also performed. LB significantly increased NS-SV-AC cell proliferation, fluid secretion, and AQP-5 expression. In NOD/SCID mice, LB reduced anti-SSA/Ro and anti-SSB/La antibodies, tumor necrosis factor-α, interferon-γ, and interleukin-6, while increasing AQP-5 and M3R expression. This resulted in increased salivary secretion and reduced glandular inflammation. LB extract appears promising for managing oral health by enhancing salivation, upregulating AQP-5, and modulating immune-inflammatory responses.